The Africans: A triple heritage : Nature of continent and Legacy of lifestyle - Mazrui Ali (The Africans: a tripple heritage, 1986)
The africans asks hard questions as it examines the complexities of a continent influenced by its indigenous roots, Islam and European Christianity.